(untitled) (Eurasian Journal of Philology Science and Education, 2021)
This article describes the social life, the fate of the nation, the state of the people, which became the basis of poetic works during the years of independence. Since then, humanity has been fighting tirelessly for its freedom, for the independence of its country. The study of whether poetic works influenced the path of development, formation, ascent, and what changes and features brought independence to the work of the Akyns, was part of the spiritual heritage of the modern sovereign state – historical events caused by the thirst for liberation and the social struggle for its achievement. To consider the features of the poetic direction, the topics covered by the poets of the period of independence, to determine the place of the creativity of individual akyns in the history of Kazakh literature. Comprehension of poetic features of poetic works during the years of Independence, determination of the place of creativity of individual poets in the history of Kazakh literature. The purpose of the study: to conduct a comprehensive study of the artistic nature and genre-poetic-textual features of Kazakh poetry over the years of independence. Carry out works that correspond to the nature of development, the main channels of formation and creativity of young poets who came to the world of poetry during the years of independence. The foundations of genre and poetic transformations in Kazakh poetry during the period of independence encode cultural intensification, give poetic creativity an individual meaning, bring together national and related genres in the context of a modern text, emphasize the artistic and aesthetic power of modern language culture